DEVELOPMENT DYNAMICS OF THE TRANSPORT NETWORK IN MAŁOPOLSKIE VOIVODESHIP IN THE PERIOD 2002–2014 - Szewczyk, Janina; Wieser, Krzysztof (Acta Scientiarum Polonorum. Oeconomia, 2018)
Transport infrastructure is necessary for the proper functioning of the economy and performs a key role in its development. In this paper particular attention was paid to the development of a linear road transport infrastructure. The research is based on the analysis of statistical data from the databases of the Eurostat and the Polish Central Statistical Office (GUS). The values of road density ratios, which are expressed in kilometers of roads per 100 km2 of the surface area, point to the dominance of Małopolskie Voivodeship over the national average. In respect of annual increases in the length of motorways and expressways, Małopolskie ranks high among western voivodeships, and exceeds the average annual domestic increase by 0.3 km of motorway/expressway section. The density of railroads is high – in this aspect only south-western voivodeships rank higher than Małopolskie Voivodship. Water transport in this region was limited to the operation of one waterway. Air transport in the voivodeship is based on the operation of one regional airport in Kraków-Balice.